2005
DOI: 10.1088/0954-3899/31/10/091
|View full text |Cite
|
Sign up to set email alerts
|

Quadrupole moment measurements of TSD1 and TSD2 bands in167Lu

Abstract: The triaxial strongly deformed (TSD) bands in 167Lu were populated by the 123Sb(48Ca, 4n) reaction with a beam energy of 203 MeV. Gamma rays, requiring five fold or more in prompt coincidence, were detected with the Gammasphere spectrometer. Of particular interests are TSD bands 1 and 2 which have previously been interpreted as zero phonon and one phonon wobbling bands, respectively. Using the Doppler shift attenuation method (DSAM), a preliminary transition quadrupole moment of 6.9+0.3−0.3 eb was extracted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The cranking formalism has predicted pronounced minima around (ε 2 ,γ ) ∼ (0.4,20 • ) which are caused by shell gaps for proton numbers Z = 71 and 72, and neutron numbers N = 94 and 97 [40,48]. The observed markedly enhanced transition quadrupole moments of the TSD bands comparing with the ND bands in 163,164,165 Lu [49][50][51][52] shows that these bands have an enhanced deformation. Furthermore, the wobbling bands observed in 163,165,167 Lu and possibly 161 Lu can only be formed at triaxial deformation.…”
Section: E Tsd Bandsmentioning
confidence: 99%
“…The cranking formalism has predicted pronounced minima around (ε 2 ,γ ) ∼ (0.4,20 • ) which are caused by shell gaps for proton numbers Z = 71 and 72, and neutron numbers N = 94 and 97 [40,48]. The observed markedly enhanced transition quadrupole moments of the TSD bands comparing with the ND bands in 163,164,165 Lu [49][50][51][52] shows that these bands have an enhanced deformation. Furthermore, the wobbling bands observed in 163,165,167 Lu and possibly 161 Lu can only be formed at triaxial deformation.…”
Section: E Tsd Bandsmentioning
confidence: 99%
“…Measurements of the life-times in the TSD band and the yrast ND band have been presented [58,59]. However, these life-times are associated with large uncertainties and appear somewhat confusing when compared with the present calculations.…”
Section: Discussionmentioning
confidence: 72%
“…Finally, the experimental value of Qt for the TSD1 band is shown. It is obtained as an average over the most intense transitions, see [59].…”
Section: The 541 Bands At Higher Energymentioning
confidence: 99%
“…It is found that typical values for normal deformed bands fall in the range 6-7 eb [40,41], while the values for the strongly deformed bands in [168][169][170][171][172][173][174] Hf fall in the range fall in the range 11-14 eb. The TSD1 bands in 165,167 Lu do also fall in the range 6-7 eb [42,43], indicating that they have a similar deformation as the ND bands. The values for the TSD1 band in 163 Lu are lower than the early measurements [2] but appear somewhat higher than in 165,167 Lu.…”
Section: Measured Transition Quadrupole Moments Q Tmentioning
confidence: 89%